Die geboortedatum van Christus as 'n historiese probleem - F. P. Retief; J. F. G. Cilliers; M. J. H. Hoffman (Acta Theologica)
In the past attempts to establish the date of birth of Jesus have led to proposed dates as early as 20 BC but also as late as 2 AD. In this article the limited primary historical sources are carefully examined and contemporary interpretations of these sources are critically reviewed. Astronomical information concerning the so-called “star of Bethlehem” is examined to determine to what extent it can contribute to a more accurate pinpointing of the date of birth. This examination leads to the conclusion that the date of birth of Jesus should be placed in 5 BC or 6 BC (between March and November).